14-3-3-protein regulates Nedd4-2 by modulating interactions between HECT and WW domains - Pavel Pohl (Nature Portfolio, 2021)
Pohl et al. investigated the structural basis of Nedd4-2 regulation by 14-3-3 and found that phosphorylated Ser342 and Ser448 are the main residues that facilitate 14-3-3 binding to Nedd4-2. The authors propose that the Nedd4-2:14-3-3 complex then stimulates a structural rearrangement of Nedd4-2 through inhibiting interaction of its structured domains.